SOIL EROSION OVER DIFFERENT SLOPES UNDER PINE STANDS - Rosmaeni Rosmaeni; Daud Malamassam; Hazairin Zubair; Mursyid Mursyid (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2022)
Forests have an important role in controlling soil erosion. Pine stands are considered effective in controlling erosion due to high interception and thick litter. This study compares the level of erosion on land with a slope > 40% to land with a slope <40%, as one of the references used in reviewing standards for determining the slope of a protected forest area. The study was conducted from November 2016 to February 2017, under Pinus merkusii stand in the Education Forest of Hasanuddin University in Maros Regency. Erosion was measured in a land of 22 m x 4 m having long slopes > 40% and < 40% with 3 replicates. Surface runoff was measured during rain and suspension levels was determined based on a dry oven heated at 105°C. Actual erosion (gr) is calculated by multiplying total runoff volume (m3/plot) by suspension level (gr/m3). The results show the average erosion on the slopes >40% was 54.94 g/plot or 0.006 tons/ha while on the slopes <40% was 36.74 g/plot or 0.004 tons/ha. The average difference of the two test results, with a 95% confidence interval, shows differences in the erosion average on the slopes> 40% and <40%. However, when there is an increase in the percentage of canopy cover the erosion becomes smaller even on the slopes > 40%. This research can be used as a reference for considering the increase in the upper limit of the slope of the protected forest area, and the need for further evaluation on the existing upper limit value.